Smartphone dependency latent profile classification and association with emotional and behavioral difficulties among high school students in Korea - Eunjoo Kim; Min Kyung Song (지역사회간호학회지, 2024)
Purpose: The pervasive integration of smartphones into adolescents’ daily lives has resulted in a concerning upsurge in smartphone dependency among high school students. Due to the diverse types and severity levels of smartphone dependency, there is a critical need for research to explore its heterogeneity. This study aimed to identify latent profile of smartphone dependency in high school students based on the four subdomains of smartphone dependency: disturbance of adaptive functions, virtual life orientation, withdrawal, and tolerance. In addition, we explored how emotional and behavioral difficulties differ according to the profiles. Methods: We used data from 2,195 Korean high school students from the Korean Children and Youth Panel Survey 2018. Latent profile analysis (LPA) was performed to identify smartphone dependency latent profile. Statistical analysis including chi-square test, Analysis of Variance (ANOVA), and ranked Analysis of Covariance (ANCOVA) confirmed differences in smartphone use characteristics and emotional-behavioral difficulties according to the classified latent profile. Results: LPA identified four distinct latent profiles of smartphone dependency among high school students; 1) Underdependent type, 2) Moderate type, 3) Habitual user type, and 4) Virtual space dependent type. The results of ranked ANCOVA, controlling for gender, geographical location, economic status, parental smartphone dependency, and relational variables, revealed that habitual user type exhibited significantly higher rates of attention deficit hyperactivity disorder, social withdrawal, and depressive symptoms compared to other types. Conclusion: The identification of these profiles provides a foundation for developing tailored intervention programs for adolescents with different levels and patterns of smartphone dependency. KCI Citation Count: 0